Transcendance et transformation de soi dans la doctrine du pur amour selon madame Guyon - Blée, Fabrice (Studies in religion, 2020)
Mindfulness meditation is very popular today but is often reduced to an immanentist perspective, suggesting that human nature in itself has the resources for its own change. From a spiritual point of view this perspective is not without danger, possibly leading to an artificial meditative emptiness. Access to a life of fullness is not without a close relationship to otherness, to the Wholly-Other, the transcendent reality at the heart of the life of prayer. Hence the importance of a dialogue between theology and health sciences about contemplative practices in order to distinguish between works and grace. This article encourages such a dialogue by exploring transcendence in the work of Madame Guyon, a French mystic of the 17th century. It provides the foundations of such a dialogue by describing the way in which she conceives the nature of the experience of transcendence, the way in which this experience involves a self-transformation, and how it fits into everyday life.